Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

Natural weathering reduces spectroscopic identifiability of common plastics - Anna E.R. Gilbert; Mark E. Hodson; Roland Kröger; W. Roland Gehrels (Environmental Pollution, 2026)

In-situ RbSr dating of the crystalline basement beneath the Amadeus Basin, Australia: Implications for the radiogenic helium generation, migration and extreme 4He accumulation - Cecilia Loyola; Juraj Farkaš; Alan S. Collins; Jason Alexander Charlwood; Sarah E. Gilbert; Peter W. Haines (Chemical Geology, 2026)

Heart rate and sub-blubber temperature in harbour seals (Phoca vitulina) measured during the moult and post-moult using implantable loggers - W. D. Paterson; L. L. Chaise; S. E. Moss; R. Milne; C. Gilbert; J. I. Currie; D. Thompson; D. J. McCafferty (Journal of Comparative Physiology B, 2026)
The moult represents an important seasonal change in the physiology of phocid seals. However, physiological measurements are challenging due to the impracticalities of instrumenting moulting animals. The aim of this study was (i) to assess the feasibility of a long-term deployment of fully implantable loggers to measure heart rate (HR) and sub-blubber temperature (T b ) in harbour seals ( Phoca vitulina ) and (ii) to compare HR and T b during moult and post-moult periods. Loggers were surgically implanted on an adult and sub-adult harbour seal in captivity. Animals healed quickly from surgery and loggers provided 65 days of continuous data before removal of the device. Results showed that in the adult when hauled out and in the water HR was lower during the moult compared with the post-moult. For the sub-adult, HR while in the water was also higher during the post-moult, however, when hauled out there was no difference in HR between the moult and post-moult periods. When hauled out, T b was greater for both animals during the moult compared with the post-moult. During haulout events, T b increased over time in both periods and T b in both animals was lower during post moult compared to the moult period. In the sub-adult, T b decreased with time in the water during the moult but showed little change during the post-moult period, whereas no temporal change was evident in the adult during either period. This study demonstrated that fully implantable loggers are a useful research tool allowing measurement of physiological parameters that are otherwise difficult to measure in pinnipeds. Physiological measurements suggested that the requirement to maintain higher skin temperature for hair growth during the moult was offset by lower metabolism to save energy in water, and on land in the case of adults. However, a decrease in body temperature with time in water in the sub-adult indicated that a smaller body size and less well-developed blubber layer is not as effective in reducing heat loss compared to adults. Future physio-logging on pinnipeds throughout their annual lifecycle may therefore benefit from similar techniques used to implant loggers.

In situ Rb–Sr geochronology records multiple fluid pulses in Neoproterozoic sequences from the Lubambe-Mingomba Cu deposits in the Zambian Copperbelt - Victor Ikechukwu Vincent; Koen Torremans; Darwinaji Subarkah; Sarah E. Gilbert; Juraj Farkaš; Alan S. Collins; Jon Stacey; Aileen L. Doran; Simon Jones; Murray W. Hitzman (Precambrian Research, 2026)

Nutritional and functional properties of defatted avocado (Persea americana) pulp cake and its application in the manufacture of cookies. - Soledad Quezada Berru; Elza Aguirre; Maykabeth W. García-Siu; John O. Arias-Nuñuvero; Any Córdova-Chang; Gilbert Rodríguez; Eudes Villanueva (Food and Humanity, 2026)

From magma to macrophage: the grand challenges of volcanic environments - Catherine A. Mériaux; Edward Ntim Gasu; Guillaume Nyagatare; Vicky Ruganzu; Philbert Ntivuguruzwa; Mwumvaneza Mutagoma; Atalay Ayele; Julyan H. E. Cartwright; Valérie Cayol; Laurent Charlet; Claudia Corradino; Antonio Costa; et al. (Bulletin of Volcanology, 2026)
The interdisciplinary study of volcanic processes, which extend across all timescales and lengths, requires a multitude of approaches, ranging from analogue and numerical modelling to observations and fieldwork and extending to mathematics. A conference was held at the East African Institute for Fundamental Research, affiliated with the University of Rwanda, a country which, along with the Democratic Republic of Congo, presents a unique geodynamic context. Located along the East African Rift, an active seismic region, Rwanda is close to two of Africa's most active volcanoes, including Nyiragongo, which overlooks Lake Kivu, a deep volcanic lake rich in dissolved carbon dioxide and methane, the latter of which is used for electricity generation. In this context, the conference addressed many “classic” volcanological topics and their modern advances, such as multiphase lava flows, subsurface magma propagation, seismic and deformation signals from a volcano, modelling of volcanic emission dispersion, and volcanic lakes. Yet, it broadened the discussion to the volcanic particle-water interface and its impact on soils, volcanoes and climate change, and volcanoes and health. This article aims to highlight and share the richness of the integration and interconnectedness of the various questions related to a volcanic environment, as well as their impact on society. Ultimately, this conference also demonstrated the importance of promoting science in Africa and developing countries so that the next generation of African researchers is equipped to address the challenges facing their nations.

Digestion of food proteins: the role of pepsin - Mengxiao Yang; Zhi Yang; David W. Everett; Elliot Paul Gilbert; Harjinder Singh; Aiqian Ye (Critical Reviews in Food Science and Nutrition, 2025)

Growth and life-history parameters of the high-value sea cucumber, Holothuria fuscogilva - Steven W. Purcell; Lea A.F. Djenidi; Hugo Denis; Florian Baletaud; Antoine Gilbert (Fisheries Research, 2025)

From boom to decline: Spatio-temporal evolution and management of New Caledonia's sea cucumber fisheries - Steven W. Purcell; Caroline Ton; Nicolas Guillemot; Antoine Gilbert (Ocean & Coastal Management, 2025)

In situ Rb–Sr dating and REE analysis of glauconites and detrital feldspars from the Ediacaran/Cambrian strata: Centralian and Adelaide Superbasins, Australia - Cecilia Loyola; Juraj Farkaš; Alan S. Collins; Sarah E. Gilbert; Charles Verdel; Stefan C. Löhr; Glenn A. Brock; Graham A. Shields; Andre Baldermann; Ahmad Redaa; Morgan Blades; Darwinaji Subarkah; et al. (Precambrian Research, 2025)

A Case of Angiotensin II Utilization for Refractory Shock in a Polysubstance Overdose - Brian W. Gilbert; Charles S. Wilson Jr; Nicholas Kim; Tessa R. Cox; Melissa V. Ortiz (Journal of Medical Toxicology, 2025)

Evaluating the Efficacy of Drone‐Based Thermal Images for Measuring Wildlife Abundance and Physiology - Wade A. Matern; Abram B. Fleishman; Ianna Gilbert; Xaun Wilson; Jean‐Marc Beddow; Isabella Garfield; Armando Ornelas; Matthew McKown; Patrick W. Robinson; Roxanne S. Beltran (Marine Mammal Science, 2025)
Although drones are a promising alternative to traditional wildlife monitoring methods, validation efforts are needed to quantify the accuracy of abundance and distribution estimates obtained from using drones. We used drones equipped with high‐resolution Red‐Green‐Blue (RGB) and thermal cameras, coupled with machine learning techniques, to assess the abundance and thermal physiology in northern elephant seals ( Mirounga angustirostris ). Aerial images of 3415 seals and measurements of ambient air temperature, wind speed, and time of day were collected during nighttime and daytime drone flights ( N = 24). Two‐dimensional polygons and surface temperatures of seals were measured from the images. Machine learning algorithms were applied to detect seals in the imagery, and model performance was evaluated. Detection was more accurate using RGB images (machine learning averaged 6.8% lower than human counts) than thermal images (16.6%). However, thermal images were useful for determining that time of day and ambient temperature (but not wind speed or body size) influenced seal external skin temperature. RGB and thermal cameras have different strengths and weaknesses that should be considered when designing research studies. Our study demonstrates that integrating drones, thermal imaging, and machine learning can promote faster, safer, cheaper, less disruptive, and more accurate wildlife monitoring and conservation efforts.

Temporal Loss of Genome‐Wide and Immunogenetic Diversity in a Near‐Extinct Parrot - Luke W. Silver; Katherine A. Farquharson; Emma Peel; M. Thomas P. Gilbert; Katherine Belov; Hernán E. Morales; Carolyn J. Hogg (Molecular Ecology, 2025)
Loss of genetic diversity threatens a species' adaptive potential and long‐term resilience. Predicted to be extinct by 2038, the orange‐bellied parrot ( Neophema chrysogaster ) is a critically endangered migratory bird threatened by numerous viral, bacterial and fungal diseases. The species has undergone multiple population crashes, reaching a low of three wild‐born females and 13 males in 2016, and is now represented by only a single wild population and individuals in the captive breeding program. Here we used our high‐quality long‐read reference genome, and contemporary ( N = 19) and historical ( N = 16) resequenced genomes from as early as 1829, to track the long‐term genomic erosion and immunogenetic diversity decline in this species. 62% of genomic diversity was lost between historical (mean autosomal heterozygosity = 0.00149 ± 0.000699 SD) and contemporary (0.00057 ± 0.000026) parrots. A greater number and length of runs of homozygosity in contemporary samples were also observed. A temporal reduction in the number of alleles at Toll‐like receptor genes was found (historical average alleles = 5.78 ± 2.73; contemporary = 3.89 ± 2.10), potentially exacerbating disease susceptibility in the contemporary population. Of particular concern is the new threat of avian influenza strain (HPAI) to Australia. We discuss the conservation implications of our findings and propose that hybridisation and synthetic biology may be required to address the catastrophic loss of genetic diversity that has occurred in this species in order to prevent extinction.

Historical genomic variation of Eurasian otters (Lutra lutra) in Britain, from hunting trophies - Sarah J. du Plessis; Nuno F. Martins; Xin Sun; Sarah S. T. Mak; David W. G. Stanton; Klaus-Peter Koepfli; Elizabeth A. Chadwick; M. P. Thomas Gilbert; Frank Hailer (Conservation Genetics Resources, 2025)
Genomic data from historical specimens can provide insights into populations and processes no longer evident from modern samples. Identifying viable sources of historical DNA is key to this. Here we aimed to explore the viability of trophy hunting paws as sources of historical DNA, and to use this data for preliminary analyses to evaluate changes in population structuring over time. We aimed to search for the presence of genomic signals of the putative recent introduction of Eurasian otters ( Lutra lutra ) from Asia to the UK previously identified using modern data, by analysis of two trophy paws from 1929 to 1952. Substantial proportions of endogenous DNA (77–85%) were identified in both samples for which genomic DNA extraction and sequencing was attempted, illustrating the potential of such specimens for historical DNA research. Autosomal variation suggests that the historical specimens cluster closest to modern specimens from Wales, and not with the variation identified in the East of England, putatively associated with the recent introduction of Eurasian otters from Asia. Similarly, the divergent mitochondrial lineage found in modern otters from the East of England and Asia, was not found in the historical British specimens. Although limited inferences can be made from a sample size of two, this preliminary dataset indicates the huge potential of historical trophy paw samples to assess past population genetic dynamics, calling for further research in this area.

Mindful Eating and Diet Quality Among US Adults With Lower Incomes - Nour M. Hammad; Melissa J. Slotnick; Teresa T. Fung; Diane Gilbert-Diamond; Lilian W.Y. Cheung; Cindy W. Leung (Journal of the Academy of Nutrition and Dietetics, 2025)

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Probing structural modification of milk proteins in the presence of pepsin and/or acid using small- and ultra-small-angle neutron scattering - Mengxiao Yang; Aiqian Ye; Zhi Yang; David W. Everett; Liliana de Campo; Harjinder Singh; Elliot Paul Gilbert (Food Hydrocolloids, 2025)

Host Species–Microbiome Interactions Contribute to Sphagnum Moss Growth Acclimation to Warming - Tatjana Živković; Alyssa A. Carrell; Gustaf Granath; A. Jonathan Shaw; Dale A. Pelletier; Christopher W. Schadt; Dawn M. Klingeman; Mats B. Nilsson; Manuel Helbig; Denis Warshan; Ingeborg J. Klarenberg; Daniel Gilbert; et al. (Global Change Biology, 2025)
Sphagnum moss is the dominant plant genus in northern peatlands responsible for long‐term carbon accumulation. Sphagnum hosts diverse microbial communities (microbiomes), and its phytobiome (plant host + constituent microbiome + environment) plays a key role in nutrient acquisition along with carbon cycling. Climate change can modify the Sphagnum ‐associated microbiome, resulting in enhanced host growth and thermal acclimation as previously shown in warming experiments. However, the extent of microbiome benefits to the host and the influence of host–microbe specificity on Sphagnum thermal acclimation remain unclear. Here, we extracted Sphagnum microbiomes from five donor species of four peatland warming experiments across a latitudinal gradient and applied those microbiomes to three germ‐free Sphagnum species grown across a range of temperatures in the laboratory. Using this experimental system, we test if Sphagnum 's growth response to warming depends on the donor and/or recipient host species, and we determine how the microbiome's growth conditions in the field affect Sphagnum host growth across a range of temperatures in the laboratory. After 4 weeks, we found that the highest growth rate of recipient Sphagnum was observed in treatments of matched host–microbiome pairs, with rates approximately 50% and 250% higher in comparison to maximum growth rates of non‐matched host–microbiome pairs and germ‐free Sphagnum , respectively. We also found that the maximum growth rate of host–microbiome pairs was reached when treatment temperatures were close to the microbiome's native temperatures. Our study shows that Sphagnum 's growth acclimation to temperature is partially controlled by its constituent microbiome. Strong Sphagnum host–microbiome species specificity indicates the existence of underlying, unknown physiological mechanisms that may drive Sphagnum 's ability to acclimatize to elevated temperatures. Together with rapid acclimation of the microbiome to warming, these specific microbiome–plant associations have the potential to enhance peatland resilience in the face of climate change.

Length–Weight Relationships of the Prized Sea Cucumber Holothuria lessoni from In Situ and Ex Situ Measurements - Lea A. F. Djenidi; Steven W. Purcell; Aaron W. Thornton; Hugues Gossuin; Antoine Gilbert (Journal of Marine Science and Engineering, 2024)
Fisheries science draws on morphometric data for stock assessments. Length–weight relationships are essential for estimating body weight from length measurements taken either underwater (in situ) or out of the water (ex situ). We examined morphometric models for the high-valued sea cucumber, Holothuria lessoni. From 77 specimens captured in 2024 (mean weight ± SD: 1774 ± 372 g), we measured body length and width in situ and ex situ, then weighed the animals ex situ. We compared morphometric models using four biometric parameters. The fitted relationships were more statistically significant (p

Potential for large losses of carbon from non-native conifer plantations on deep peat over decadal timescales - Thomas J. Sloan; Joshua Ratcliffe; Russell Anderson; W. Roland Gehrels; Peter Gilbert; Dmitri Mauquoy; Anthony J. Newton; Richard J. Payne; Justyna Serafin; Roxane Andersen (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Comparison of two carbonaceous supported Fe-rich adsorbents for arsenate removal: A functionalisation and mechanistic study with applicability to groundwater treatment - Sabolc Pap; Maja Turk Sekulic; Hai Nguyen Tran; Huan-Ping Chao; Peter J. Gilbert; Stuart W. Gibb; Mark A. Taggart (Chemosphere, 2024)

Pepsin-induced hydrolysis and coagulation of proteins in goat, sheep and cow milk - Mengxiao Yang; Aiqian Ye; Elliot Paul Gilbert; Zhi Yang; David W. Everett; Harjinder Singh (International Dairy Journal, 2024)

A century of statistical Ecology - Neil A. Gilbert; Bruna R. Amaral; Olivia M. Smith; Peter J. Williams; Sydney Ceyzyk; Samuel Ayebare; Kayla L. Davis; Wendy Leuenberger; Jeffrey W. Doser; Elise F. Zipkin (Ecology, 2024)
As data and computing power have surged in recent decades, statistical modeling has become an important tool for understanding ecological patterns and processes. Statistical modeling in ecology faces two major challenges. First, ecological data may not conform to traditional methods, and second, professional ecologists often do not receive extensive statistical training. In response to these challenges, the journal Ecology has published many innovative statistical ecology papers that introduced novel modeling methods and provided accessible guides to statistical best practices. In this paper, we reflect on Ecology 's history and its role in the emergence of the subdiscipline of statistical ecology, which we define as the study of ecological systems using mathematical equations, probability, and empirical data. We showcase 36 influential statistical ecology papers that have been published in Ecology over the last century and, in so doing, comment on the evolution of the field. As data and computing power continue to increase, we anticipate continued growth in statistical ecology to tackle complex analyses and an expanding role for Ecology to publish innovative and influential papers, advancing the discipline and guiding practicing ecologists.

The impact of marital status on tumor aggressiveness, treatment, and screening among black and white men diagnosed with prostate cancer - Saira Khan; Lindsay Fuzzell; Marvin Langston; Yunan Han; Justin X. Moore; Keon Gilbert; Siobhan Sutcliffe; Jeannette T. Bensen; James L. Mohler; Elizabeth T.H. Fontham; Lixin Song; Marquita W. Lewis-Thames (Cancer Causes & Control, 2024)

Background contrast affects detection and recognition of courting wolf spiders by intended and unintended receivers - George W. Uetz; Rachel Gilbert; Rebecca Wilson; Jacqueline Mann; Joseph Macedonia; David L. Clark (Behavioral Ecology and Sociobiology, 2024)
We used video playback of courting male Schizocosa ocreata wolf spiders to examine responses of intended receivers (conspecific females) and eavesdroppers (competitor males, predatory spiders, toads) to manipulations of spider color (natural color, monochromatic gray, monochromatic RBG average) displayed against complex leaf litter backgrounds (color, grayscale). Models of chromatic and achromatic contrast between spider stimuli and backgrounds were used to predict receiver responses. The results support the hypothesis that interactions between spider and background coloration affect detection and recognition, although responses varied with receiver type. Detection responses of intended receivers (female S. ocreata ) did not fit predictions of the chromatic contrast model in some cases, but showed a fair fit to the achromatic model. Detection responses of social eavesdroppers (male S. ocreata ) fit the chromatic and achromatic contrast models slightly better than did female responses (poor fit and very good fit, respectively). Eavesdropping wolf spider predators ( Rabidosa ) exhibited detection responses that significantly matched predictions of the chromatic (very good fit) and achromatic (excellent fit) models. Whereas jumping spiders ( Phidippus ) showed a good fit to the chromatic and achromatic contrast models, toad predators had a good fit only to the chromatic model. Recognition responses revealed a different pattern of fit to the chromatic and achromatic models across receiver types, although Rabidosa again indicated a significant fit to both models. Taken together, the results of this study identify both chromatic and achromatic features of spider appearance as likely explanations for differences in behavioral responses of intended and unintended receivers. This outcome suggests the possibility that both sexual and natural selection likely target different features of male appearance during courtship.

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Farm level bio-economic modelling of aquatic animal disease and health interventions - E.J. Peeler; R. Caballero-Celli; C.E.S. Davila; A.C. Canales Gomez; W. Gilbert; M. Gómez-Sánchez; Huntington; V.T. Phan; J. Rushton; R.S. Schrijver; A. Kennerley (Preventive Veterinary Medicine, 2023)

Restoration ecology through the lens of coexistence theory - Lauren M. Hallett; Lina Aoyama; György Barabás; Benjamin Gilbert; Loralee Larios; Nancy Shackelford; Chhaya M. Werner; Oscar Godoy; Emma R. Ladouceur; Jacob E. Lucero; Christopher P. Weiss-Lehman; Jonathan M. Chase; et al. (Trends in Ecology & Evolution, 2023)

Implications of outgroup selection in the phylogenetic inference of hominoids and fossil hominins - Nicholas W. Post; Christopher C. Gilbert; Kelsey D. Pugh; Carrie S. Mongle (Journal of Human Evolution, 2023)

Effects of Leaf Moisture on Transmission and Detection of Communication by a Wolf Spider - George W. Uetz; Alexander L. Sweger; Emmanuel Bagirov; Madeline Lallo; Christina Horton; Olivia Bauer-Nilsen; Riddhi Upadhyaya; Abbey Miles; Rachel Gilbert (Journal of Insect Behavior, 2023)

Effect of ingestion temperature on the pepsin-induced coagulation and the in vitro gastric digestion behavior of milk - Mengxiao Yang; Aiqian Ye; Zhi Yang; David W. Everett; Elliot Paul Gilbert; Harjinder Singh (Food Hydrocolloids, 2023)

Daily activity timing in the Anthropocene - Neil A. Gilbert; Kate A. McGinn; Laura A. Nunes; Amy A. Shipley; Jacy Bernath-Plaisted; John D.J. Clare; Penelope W. Murphy; Spencer R. Keyser; Kimberly L. Thompson; Scott B. Maresh Nelson; Jeremy M. Cohen; Ivy V. Widick; et al. (Trends in Ecology & Evolution, 2023)

Pepsin-induced coagulation of casein micelles: Effect of whey proteins and heat treatment - Mengxiao Yang; Aiqian Ye; Zhi Yang; David W. Everett; Elliot Paul Gilbert; Harjinder Singh (Food Chemistry, 2023)

Assessing homogeneity of land surface air temperature observations using sparse‐input reanalyses - Ian Gillespie; Leo Haimberger; Gilbert P. Compo; Peter W. Thorne (International Journal of Climatology, 2023)
State‐of‐the‐art homogenisation approaches for any test site rely upon the availability of a sufficient number of neighbouring sites with similar climatic conditions and a sufficient quantity of overlapping measurements. These conditions are not always met, particularly in poorly sampled regions and epochs. Modern sparse‐input reanalysis products which are constrained by observed sea surface temperatures, sea‐ice and surface pressure observations, continue to improve, offering independently produced surface temperature estimates back to the early 19th century. This study undertakes an exploratory analysis on the applicability of sparse‐input reanalysis to identify breakpoints in available basic station data. Adjustments are then applied using a variety of reanalysis and neighbour‐based approaches to produce four distinct estimates. The methodological independence of the approach may offer valuable insights into historical data quality issues. The resulting estimates are compared to Global Historical Climatology Network version 4 (GHCNMv4) at various aggregations. Comparisons are also made with five existing global land surface monthly time series. We find a lower rate of long‐term warming which principally arises in differences in estimated behaviour prior to the early 20th century. Differences depend upon the exact pair of estimates, varying between 15 and 40% for changes from 1850–1900 to 2005–2014. Differences are much smaller for metrics starting after 1900 and negligible after 1950. Initial efforts at quantifying parametric uncertainty suggest this would be substantial and may lead to overlap between these new estimates and existing estimates. Further work would be required to use these data products in an operational context. This would include better understanding the reasons for apparent early period divergence including the impact of spatial infilling choices, quantification of parametric uncertainty, and a means to update the product post‐2015 when the NOAA‐CIRES‐DOE 20CRv3 sparse input reanalysis product, upon which they are based, presently ceases.

Associations between Afrotropical bats, eukaryotic parasites, and microbial symbionts - Holly L. Lutz; Jack A. Gilbert; Carl W. Dick (Molecular Ecology, 2022)
Skin is the largest mammalian organ and the first defensive barrier against the external environment. The skin and fur of mammals can host a wide variety of ectoparasites, many of which are phylogenetically diverse, specialized, and specifically adapted to their hosts. Among hematophagous dipteran parasites, volatile organic compounds (VOCs) are known to serve as important attractants, leading parasites to compatible sources of blood meals. VOCs have been hypothesized to be mediated by host‐associated bacteria, which may thereby indirectly influence parasitism. Host‐associated bacteria may also influence parasitism directly, as has been observed in interactions between animal gut microbiota and malarial parasites. Hypotheses relating bacterial symbionts and eukaryotic parasitism have rarely been tested among humans and domestic animals, and to our knowledge have not been tested in wild vertebrates. In this study, we used Afrotropical bats, hematophagous ectoparasitic bat flies, and haemosporidian (malarial) parasites vectored by bat flies as a model to test the hypothesis that the vertebrate host microbiome is linked to parasitism in a wild system. We identified significant correlations between bacterial community composition of the skin and dipteran ectoparasite prevalence across four major bat lineages, as well as striking differences in skin microbial network characteristics between ectoparasitized and nonectoparasitized bats. We also identified links between the oral microbiome and presence of malarial parasites among miniopterid bats. Our results support the hypothesis that microbial symbionts may serve as indirect mediators of parasitism among eukaryotic hosts and parasites.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Does a Trawl Ban Benefit Commercially Important Decapoda and Stomatopoda in Hong Kong? - Lily S. R. Tao; Gilbert C. S. Lui; Kingsley J. H. Wong; Tommy T. Y. Hui; Yanny K. Y. Mak; Ronia C.-t Sham; Jason K. C. Yau; William W. L. Cheung; Kenneth M. Y. Leung (Ecosystems, 2021)
Crustaceans were among the most valuable fishery resources in Hong Kong. However, the unrestricted and intensive use of different fishing gears, especially bottom trawling, has led to the depletion of commercially important crustaceans in Hong Kong since the 1980s. This study investigated whether commercial crustaceans recovered after the implementation of a permanent Hong Kong-wide trawl ban that began on December 31, 2012. Standardized field surveys were conducted using a commercial shrimp trawler at two sites in eastern and western waters of Hong Kong before (2004) and after the trawl ban (2013–2014 and 2015–2016) and two sites in southern waters after the trawl ban. Diversity, mean size, abundance, biomass and level of disturbance of commercial crustaceans from the three periods were investigated. The eastern waters exhibited an increased diversity of crustacean assemblages in Inner Tolo, and a higher abundance and biomass of crabs were detected in Outer Tolo after the trawl ban. Reduced disturbance, higher diversity in crustacean assemblages and greater abundance and biomass of predatory crabs were observed after the trawl ban in the outer estuary of western waters, and increased abundance and biomass of shrimp were detected in the inner estuary of western waters. No temporal or negative changes were detected in the southeast and southern waters of Lamma Island. The various responses of crustacean assemblages in Hong Kong waters revealed the critical role of complex interactions among multiple stresses, such as ongoing reclamation works, illegal trawling activities and increased fishing efforts using other (legal) fishing methods.

Altered frontal-mediated inhibition and white matter connectivity in pediatric chronic tic disorders - Adrienne B. Bruce; Weihong Yuan; Donald L. Gilbert; Paul S. Horn; Hannah S. Jackson; David A. Huddleston; Steve W. Wu (Experimental Brain Research, 2021)

Mycorrhizal type influences plant density dependence and species richness across 15 temperate forests - Feng Jiang; James A. Lutz; Qingxi Guo; Zhanqing Hao; Xugao Wang; Gregory S. Gilbert; Zikun Mao; David A. Orwig; Geoffrey G. Parker; Weiguo Sang; Yankun Liu; Songyan Tian; et al. (Ecology, 2021)
Recent studies suggest that the mycorrhizal type associated with tree species is an important trait influencing ecological processes such as response to environmental conditions and conspecific negative density dependence (CNDD). However, we lack a general understanding of how tree mycorrhizal type influences CNDD strength and the resulting patterns of species abundance and richness at larger spatial scales. We assessed 305 species across 15 large, stem‐mapped, temperate forest dynamics plots in Northeastern China and North America to explore the relationships between tree mycorrhizal type and CNDD, species abundance, and species richness at a regional scale. Tree species associated with arbuscular mycorrhizal (AM) fungi showed a stronger CNDD and a more positive relationship with species abundance than did tree species associated with ectomycorrhizal (ECM) fungi. For each plot, both basal area and stem abundance of AM tree species was lower than that of ECM tree species, suggesting that AM tree species were rarer than ECM tree species. Finally, ECM tree dominance showed a negative effect on plant richness across plots. These results provide evidence that tree mycorrhizal type plays an important role in influencing CNDD and species richness, highlighting this trait as an important factor in structuring plant communities in temperate forests.

A kinetic proofreading model for bispecific protein degraders - Derek W. Bartlett; Adam M. Gilbert (Journal of Pharmacokinetics and Pharmacodynamics, 2021)

Assessing potential of sparse‐input reanalyses for centennial‐scale land surface air temperature homogenisation - Ian M. Gillespie; Leo Haimberger; Gilbert P. Compo; Peter W. Thorne (International Journal of Climatology, 2021)
Observations from the historical meteorological observing network contain many artefacts of non‐climatic origin which must be accounted for prior to using these data in climate applications. State‐of‐the‐art homogenisation approaches use various flavours of pairwise comparison between a target station and candidate neighbour station series. Such approaches require an adequate number of neighbours of sufficient quality and comparability – a condition that is met for most station series since the mid‐20th Century. However, pairwise approaches have challenges where suitable neighbouring stations are sparse, as remains the case in vast regions of the globe and is common almost everywhere prior to the early 20th Century. Modern sparse‐input centennial reanalysis products continue to improve and offer a potential alternative to pairwise comparison, particularly where and when observations are sparse. They do not directly ingest or use land‐based surface temperature observations, so they are a formally independent estimate. This may be particularly helpful in cases where structurally similar changes exist across broad networks, which challenges current techniques in the absence of metadata. They also potentially offer a valuable methodologically distinct method, which would help explore structural uncertainty in homogenisation techniques. The present study compares the potential of spatially‐interpolated sparse‐input reanalysis products to neighbour‐based approaches to perform homogenisation of global monthly land surface air temperature records back to 1850 based upon the statistical properties of station‐minus‐reanalysis and station‐minus‐neighbour series. This shows that neighbour‐based approaches likely remain preferable in data dense regions and epochs. However, the most recent reanalysis product, NOAA‐CIRES‐DOE 20CRv3, is potentially preferable in cases where insufficient neighbours are available. This may in particular affect long‐term global average estimates where a small number of long‐term stations in data sparse regions will make substantial contributions to global estimates and may contain missed data artefacts in present homogenisation approaches.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Climate and local environment structure asynchrony and the stability of primary production in grasslands - Benjamin Gilbert; Andrew S. MacDougall; Taku Kadoya; Munemitsu Akasaka; Joseph R. Bennett; Eric M. Lind; Habacuc Flores‐Moreno; Jennifer Firn; Yann Hautier; Elizabeth T. Borer; Eric W. Seabloom; Peter B. Adler; et al. (Global Ecology and Biogeography, 2020)
Aim Climate variability threatens to destabilize production in many ecosystems. Asynchronous species dynamics may buffer against such variability when a decrease in performance by some species is offset by an increase in performance of others. However, high climatic variability can eliminate species through stochastic extinctions or cause similar stress responses among species that reduce buffering. Local conditions, such as soil nutrients, can also alter production stability directly or by influencing asynchrony. We test these hypotheses using a globally distributed sampling experiment. Location Grasslands in North America, Europe and Australia. Time period Annual surveys over 5 year intervals occurring between 2007 and 2014. Major taxa studied Herbaceous plants. Methods We sampled annually the per species cover and aboveground community biomass [net primary productivity (NPP)], plus soil chemical properties, in 29 grasslands. We tested how soil conditions, combined with variability in precipitation and temperature, affect species richness, asynchrony and temporal stability of primary productivity. We used bivariate relationships and structural equation modelling to examine proximate and ultimate relationships. Results Climate variability strongly predicted asynchrony, whereas NPP stability was more related to soil conditions. Species richness was structured by both climate variability and soils and, in turn, increased asynchrony. Variability in temperature and precipitation caused a unimodal asynchrony response, with asynchrony being lowest at low and high climate variability. Climate impacted stability indirectly, through its effect on asynchrony, with stability increasing at higher asynchrony owing to lower inter‐annual variability in NPP. Soil conditions had no detectable effect on asynchrony but increased stability by increasing the mean NPP, especially when soil organic matter was high. Main conclusions We found globally consistent evidence that climate modulates species asynchrony but that the direct effect on stability is low relative to local soil conditions. Nonetheless, our observed unimodal responses to variability in temperature and precipitation suggest asynchrony thresholds, beyond which there are detectable destabilizing impacts of climate on primary productivity.

Modelling Eurasian beaver foraging habitat and dam suitability, for predicting the location and number of dams throughout catchments in Great Britain - Hugh A. Graham; Alan Puttock; William W. Macfarlane; Joseph M. Wheaton; Jordan T. Gilbert; Róisín Campbell-Palmer; Mark Elliott; Martin J. Gaywood; Karen Anderson; Richard E. Brazier (European Journal of Wildlife Research, 2020)
Eurasian beaver ( Castor fiber ) populations are expanding across Europe. Depending on location, beaver dams bring multiple benefits and/or require management. Using nationally available data, we developed: a Beaver Forage Index (BFI), identifying beaver foraging habitat, and a Beaver Dam Capacity (BDC) model, classifying suitability of river reaches for dam construction, to estimate location and number of dams at catchment scales. Models were executed across three catchments, in Great Britain (GB), containing beaver. An area of 6747 km 2 was analysed for BFI and 16,739 km of stream for BDC. Field surveys identified 258 km of channel containing beaver activity and 89 dams, providing data to test predictions. Models were evaluated using a categorical binomial Bayesian framework to calculate probability of foraging and dam construction. BFI and BDC models successfully categorised the use of reaches for foraging and damming, with higher scoring reaches being preferred. Highest scoring categories were ca. 31 and 79 times more likely to be used than the lowest for foraging and damming respectively. Zero-inflated negative binomial regression showed that modelled dam capacity was significantly related ( p = 0.01) to observed damming and was used to predict numbers of dams that may occur. Estimated densities of dams, averaged across each catchment, ranged from 0.4 to 1.6 dams/km, though local densities may be up to 30 dams/km. These models provide fundamental information describing the distribution of beaver foraging habitat, where dams may be constructed and how many may occur. This supports the development of policy and management concerning the reintroduction and recolonisation of beaver.

Ancient DNA suggests modern wolves trace their origin to a Late Pleistocene expansion from Beringia - Liisa Loog; Olaf Thalmann; Mikkel‐Holger S. Sinding; Verena J. Schuenemann; Angela Perri; Mietje Germonpré; Herve Bocherens; Kelsey E. Witt; Jose A. Samaniego Castruita; Marcela S. Velasco; Inge K. C. Lundstrøm; Nathan Wales; et al. (Molecular Ecology, 2020)
Grey wolves ( Canis lupus ) are one of the few large terrestrial carnivores that have maintained a wide geographical distribution across the Northern Hemisphere throughout the Pleistocene and Holocene. Recent genetic studies have suggested that, despite this continuous presence, major demographic changes occurred in wolf populations between the Late Pleistocene and early Holocene, and that extant wolves trace their ancestry to a single Late Pleistocene population. Both the geographical origin of this ancestral population and how it became widespread remain unknown. Here, we used a spatially and temporally explicit modelling framework to analyse a data set of 90 modern and 45 ancient mitochondrial wolf genomes from across the Northern Hemisphere, spanning the last 50,000 years. Our results suggest that contemporary wolf populations trace their ancestry to an expansion from Beringia at the end of the Last Glacial Maximum, and that this process was most likely driven by Late Pleistocene ecological fluctuations that occurred across the Northern Hemisphere. This study provides direct ancient genetic evidence that long‐range migration has played an important role in the population history of a large carnivore, and provides insight into how wolves survived the wave of megafaunal extinctions at the end of the last glaciation. Moreover, because Late Pleistocene grey wolves were the likely source from which all modern dogs trace their origins, the demographic history described in this study has fundamental implications for understanding the geographical origin of the dog.

Interaction of APOE, cerebral blood flow, and cortical thickness in the entorhinal cortex predicts memory decline - Chelsea C. Hays; Zvinka Z. Zlatar; M.J. Meloy; Mark W. Bondi; Paul E. Gilbert; Thomas Liu; Jonathan L. Helm; Christina E. Wierenga (Brain Imaging and Behavior, 2020)

Conservation triage at the trailing edge of climate envelopes - Sophie L. Gilbert; Kate Broadley; Darcy Doran‐Myers; Amanda Droghini; Jessica A. Haines; Anni Hämäläinen; Clayton T. Lamb; Eric W. Neilson; Stan Boutin (Conservation Biology, 2020)

Oiling of American white pelicans, common loons, and northern gannets in the winter following the Deepwater Horizon (MC252) oil spill - J. D. Paruk; I. J. Stenhouse; B. J. Sigel; E. M. Adams; W. A. Montevecchi; D. C. Evers; A. T. Gilbert; M. Duron; D. Long; J. Hemming; P. Tuttle (Environmental Monitoring and Assessment, 2019)
The Natural Resource Damage Assessment and Restoration Trustees for the Deepwater Horizon oil spill assessed the external oiling of migratory bird species dependent on open water in the Gulf of Mexico following the aforementioned spill. The assessment was designed to evaluate birds that use open water during the winter within 40 km of the Gulf shoreline. We focused on the American white pelican ( Pelecanus erythrorhynchos ), common loon ( Gavia immer ), and northern gannet ( Morus bassanus ). Point counts (pelican, loon) or strip transects (gannet) were used and each target species was assessed for oiling (unoiled, trace, light, moderate, or heavy amounts) and photographed. Due to distance at sighting and/or poor visibility, not all visible birds were assessed. The percentage of birds oiled varied by species, with the common loon being the highest (23.6%), followed by American white pelican (16.9%), and northern gannet (6.9%). Most of the American white pelicans and common loons had trace (83% and 72%, respectively) or light levels (11% and 24%, respectively) of oiling. The northern gannet had just trace levels of oiling. Some pelicans (6%) and loons (4%) had moderate amounts of oiling. Based on expert derived-mortality estimates and our estimates of oil exposure, we used Monte Carlo simulations to predict expected decreases of 2.5%, 4%, and 11% in the observed population for the northern gannet, American white pelican, and common loon, respectively. While these values are underestimates of the true values given the long time lag (10–12 months) between the oil spill and the assessment, these data represent some of the few estimates of exposure for these species and describe minimum risk estimates to these species.

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Spatial ecology of urban striped skunks (Mephitis mephitis) in the Northern Great Plains: a framework for future oral rabies vaccination programs - Anna L. Schneider; Amy T. Gilbert; W. David Walter; Gregory S. Vandeberg; Jason R. Boulanger (Urban Ecosystems, 2019)

Host‐derived population genomics data provides insights into bacterial and diatom composition of the killer whale skin - Rebecca Hooper; Jaelle C. Brealey; Tom van der Valk; Antton Alberdi; John W. Durban; Holly Fearnbach; Kelly M. Robertson; Robin W. Baird; M. Bradley Hanson; Paul Wade; M. Thomas P. Gilbert; Phillip A. Morin; et al. (Molecular Ecology, 2019)
Recent exploration into the interactions and relationship between hosts and their microbiota has revealed a connection between many aspects of the host's biology, health and associated micro‐organisms. Whereas amplicon sequencing has traditionally been used to characterize the microbiome, the increasing number of published population genomics data sets offers an underexploited opportunity to study microbial profiles from the host shotgun sequencing data. Here, we use sequence data originally generated from killer whale Orcinus orca skin biopsies for population genomics, to characterize the skin microbiome and investigate how host social and geographical factors influence the microbial community composition. Having identified 845 microbial taxa from 2.4 million reads that did not map to the killer whale reference genome, we found that both ecotypic and geographical factors influence community composition of killer whale skin microbiomes. Furthermore, we uncovered key taxa that drive the microbiome community composition and showed that they are embedded in unique networks, one of which is tentatively linked to diatom presence and poor skin condition. Community composition differed between Antarctic killer whales with and without diatom coverage, suggesting that the previously reported episodic migrations of Antarctic killer whales to warmer waters associated with skin turnover may control the effects of potentially pathogenic bacteria such as Tenacibaculum dicentrarchi . Our work demonstrates the feasibility of microbiome studies from host shotgun sequencing data and highlights the importance of metagenomics in understanding the relationship between host and microbial ecology.

The artificial humic substance HS1500 does not inhibit photosynthesis of the green alga Desmodesmus armatus in vivo but interacts with the photosynthetic apparatus of isolated spinach thylakoids in vitro - Matthias Gilbert; Hanno Bährs; Christian E. W. Steinberg; Christian Wilhelm (Photosynthesis Research, 2018)

What are the Conditions of Riparian Ecosystems? Identifying Impaired Floodplain Ecosystems across the Western U.S. Using the Riparian Condition Assessment (RCA) Tool - William W. Macfarlane; Jordan T. Gilbert; Joshua D. Gilbert; William C. Saunders; Nate Hough-Snee; Chalese Hafen; Joseph M. Wheaton; Stephen N. Bennett (Environmental Management, 2018)

Ectopic, retroperitoneal adrenocortical carcinoma in the setting of Lynch syndrome - Jesse P. Wright; Kathleen W. Montgomery; Joshua Tierney; Jill Gilbert; Carmen C. Solórzano; Kamran Idrees (Familial Cancer, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

RNA interference-based silencing of the alpha-amylase (amy1) gene in Aspergillus flavus decreases fungal growth and aflatoxin production in maize kernels - Matthew K. Gilbert; Rajtilak Majumdar; Kanniah Rajasekaran; Zhi-Yuan Chen; Qijian Wei; Christine M. Sickler; Matthew D. Lebar; Jeffrey W. Cary; Bronwyn R. Frame; Kan Wang (Planta, 2018)

Evaluation of eDNA for groundwater invertebrate detection and monitoring: a case study with endangered Stygobromus (Amphipoda: Crangonyctidae) - Matthew L. Niemiller; Megan L. Porter; Jenna Keany; Heather Gilbert; Daniel W. Fong; David C. Culver; Christopher S. Hobson; K. Denise Kendall; Mark A. Davis; Steven J. Taylor (Conservation Genetics Resources, 2018)

Baseline results from the UK SIGNIFY study: a whole-body MRI screening study in TP53 mutation carriers and matched controls - Sibel Saya; Emma Killick; Sarah Thomas; Natalie Taylor; Elizabeth K. Bancroft; Jeanette Rothwell; Sarah Benafif; Alexander Dias; Christos Mikropoulos; Jenny Pope; Anthony Chamberlain; Ranga Gunapala; et al. (Familial Cancer, 2017)

Continuing influences of introduced hedgehogs Erinaceus europaeus as a predator of wader (Charadrii) eggs four decades after their release on the Outer Hebrides, Scotland - John Calladine; Elizabeth M. Humphreys; Lucy Gilbert; Robert W. Furness; Robert A. Robinson; Robert J. Fuller; Nick A. Littlewood; Robin J. Pakeman; Johanne Ferguson; Charles Thompson (Biological Invasions, 2017)

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

Emerging Opportunities for Landscape Ecological Modelling - Nicholas W. Synes; Calum Brown; Kevin Watts; Steven M. White; Mark A. Gilbert; Justin M. J. Travis (Current Landscape Ecology Reports, 2016)

A poor international standard for trap selectivity threatens carnivore conservation - Emilio Virgós; Jorge Lozano; Sara Cabezas-Díaz; David W. Macdonald; Andrzej Zalewski; Juan Carlos Atienza; Gilbert Proulx; William J. Ripple; Luis M. Rosalino; Margarida Santos-Reis; Paul J. Johnson; Aurelio F. Malo; et al. (Biodiversity and Conservation, 2016)

Remembering Jerry Lwanga: A Perspective from His Colleagues - Tony L. Goldberg; Samuel Angedakin; Gilbert M. Isabirye Basuta; Michelle Brown; Thomas M. Butynski; Colin A. Chapman; Lauren Chapman; Sholly Gunter; Innocent Kato; Jean-Michel Krief; Sabrina Krief; Joanna E. Lambert; et al. (International Journal of Primatology, 2016)

Seed-Specific Stable Expression of the α-AI1 Inhibitor in Coffee Grains and the In Vivo Implications for the Development of the Coffee Berry Borer - Érika V. S. Albuquerque; Caroline A. Bezerra; Juan V. Romero; Jorge W. A. Valencia; Arnubio Valencia-Jiménez; Lucas M. Pimenta; Aulus E. A. D. Barbosa; Maria C. M. Silva; Ana M. Meneguim; Maria Eugênia L. Sá; Gilbert Engler; Janice de Almeida-Engler; et al. (Tropical Plant Biology, 2015)

Preparation of legionaminic acid analogs of sialo-glycoconjugates by means of mammalian sialyltransferases - David C. Watson; Warren W. Wakarchuk; Christian Gervais; Yves Durocher; Anna Robotham; Steve M. Fernandes; Ronald L. Schnaar; N. Martin Young; Michel Gilbert (Glycoconjugate Journal, 2015)

Undetected Blooms in Prince William Sound: Using Multiple Techniques to Elucidate the Base of the Summer Food Web - Allison S. McInnes; Clifton C. Nunnally; Gilbert T. Rowe; Randall W. Davis; Antonietta Quigg (Estuaries and Coasts, 2015)

Elevated rates of mild cognitive impairment in HIV disease - David P. Sheppard; Jennifer E. Iudicello; Mark W. Bondi; Katie L. Doyle; Erin E. Morgan; Paul J. Massman; Paul E. Gilbert; Steven Paul Woods (Journal of NeuroVirology, 2015)

Geographic and temporal dynamics of a global radiation and diversification in the killer whale - Phillip A. Morin; Kim M. Parsons; Frederick I. Archer; María C. Ávila‐Arcos; Lance G. Barrett‐Lennard; Luciano Dalla Rosa; Sebastián Duchêne; John W. Durban; Graeme M. Ellis; Steven H. Ferguson; John K. Ford; Michael J. Ford; et al. (Molecular Ecology, 2015)
Global climate change during the Late Pleistocene periodically encroached and then released habitat during the glacial cycles, causing range expansions and contractions in some species. These dynamics have played a major role in geographic radiations, diversification and speciation. We investigate these dynamics in the most widely distributed of marine mammals, the killer whale ( Orcinus orca ), using a global data set of over 450 samples. This marine top predator inhabits coastal and pelagic ecosystems ranging from the ice edge to the tropics, often exhibiting ecological, behavioural and morphological variation suggestive of local adaptation accompanied by reproductive isolation. Results suggest a rapid global radiation occurred over the last 350 000 years. Based on habitat models, we estimated there was only a 15% global contraction of core suitable habitat during the last glacial maximum, and the resources appeared to sustain a constant global effective female population size throughout the Late Pleistocene. Reconstruction of the ancestral phylogeography highlighted the high mobility of this species, identifying 22 strongly supported long‐range dispersal events including interoceanic and interhemispheric movement. Despite this propensity for geographic dispersal, the increased sampling of this study uncovered very few potential examples of ancestral dispersal among ecotypes. Concordance of nuclear and mitochondrial data further confirms genetic cohesiveness, with little or no current gene flow among sympatric ecotypes. Taken as a whole, our data suggest that the glacial cycles influenced local populations in different ways, with no clear global pattern, but with secondary contact among lineages following long‐range dispersal as a potential mechanism driving ecological diversification.

A whole-lake experiment to control invasive rainbow smelt (Actinoperygii, Osmeridae) via overharvest and a food web manipulation - Jereme W. Gaeta; Thomas R. Hrabik; Greg G. Sass; Brian M. Roth; Stephen J. Gilbert; M. Jake Vander Zanden (Hydrobiologia, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Deriving field-based sediment quality guidelines from the relationship between species density and contaminant level using a novel nonparametric empirical Bayesian approach - Gilbert C. S. Lui; W. K. Li; Anders Bjørgesæter; Kenneth M. Y. Leung (Environmental Science and Pollution Research, 2014)

Mitogenomic insights into a recently described and rarely observed killer whale morphotype - Andrew D. Foote; Phillip A. Morin; Robert L. Pitman; María C. Ávila-Arcos; John W. Durban; Anton van Helden; Mikkel-Holger S. Sinding; M. Thomas P. Gilbert (Polar Biology, 2013)

DNA from soil mirrors plant taxonomic and growth form diversity - N. G. YOCCOZ; K. A. BRÅTHEN; L. GIELLY; J. HAILE; M. E. EDWARDS; T. GOSLAR; H. Von STEDINGK; A. K. BRYSTING; E. COISSAC; F. POMPANON; J. H. SØNSTEBØ; C. MIQUEL; et al. (Molecular Ecology, 2012)
Ecosystems across the globe are threatened by climate change and human activities. New rapid survey approaches for monitoring biodiversity would greatly advance assessment and understanding of these threats. Taking advantage of next‐generation DNA sequencing, we tested an approach we call metabarcoding: high‐throughput and simultaneous taxa identification based on a very short (usually

Mitogenome sequencing reveals shallow evolutionary histories and recent divergence time between morphologically and ecologically distinct European whitefish ( Coregonus spp.) - MAGNUS W. JACOBSEN; MICHAEL M. HANSEN; LUDOVIC ORLANDO; DORTE BEKKEVOLD; LOUIS BERNATCHEZ; ESKE WILLERSLEV; M. THOMAS P. GILBERT (Molecular Ecology, 2012)
The advent of second‐generation sequencing has made it possible to quickly and economically generate whole mitochondrial genome (mitogenome) sequences. To date, mitogenome studies of nonmodel organisms have demonstrated increased power for resolving interspecies relationships. We explored an alternate use of such data to recover relationships and population history of closely related lineages with a shallow evolutionary history. Using a GS‐FLX platform, we sequenced 106 mitogenomes from the Coregonus lavaretus (Europe) and Coregonus clupeaformis (North America) species complexes to investigate the evolutionary history of the endangered Danish North Sea houting (NSH) and other closely related Danish and Baltic European lake whitefish (ELW). Two well‐supported clades were found within both ELW and NSH, probably reflecting historical introgression via Baltic migrants. Although ELW and NSH are not reciprocally monophyletic, they share no haplotypes, suggesting recent, but strong, reproductive isolation. The divergence time between NSH and the geographically closest ELW population was estimated using IMa, assuming isolation with migration and a new mutation rate estimate chosen to avoid time‐dependency effects. The estimate of c. 2700 bp was remarkably similar to results obtained using microsatellite markers. Within North American C. clupeaformis , the divergence time between the two lineages (Atlantic and Acadian) was estimated as between 20 000 and 60 000 bp . Under the assumption that NSH and ELW colonized Denmark following the last glacial maximum, Bayesian Serial SimCoal analysis showed consistency with a scenario of long‐term stability, resulting from a rapid initial sixfold population expansion. The findings illustrate the utility of mitogenome data for resolving recent intraspecific divergence events and provide evidence for recent reproductive isolation of the phenotypically divergent NSH.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Selected coccal green algae are not affected by the humic substance Huminfeed® in term of growth or photosynthetic performance - Tobias Heinze; Hanno Bährs; Matthias Gilbert; Christian E. W. Steinberg; Christian Wilhelm (Hydrobiologia, 2012)

Trends and low-frequency variability of storminess over western Europe, 1878–2007 - Xiaolan L. Wang; Hui Wan; Francis W. Zwiers; Val R. Swail; Gilbert P. Compo; Robert J. Allan; Russell S. Vose; Sylvie Jourdain; Xungang Yin (Climate Dynamics, 2011)

An alternative view of the role of heterotrophic microbes in the cycling of organic matter in deep-sea sediments - Gilbert T. Rowe; Jody W. Deming (Marine Biology Research, 2011)

Spatial gradients of methylmercury for breeding common loons in the Laurentian Great Lakes region - David C. Evers; Kathryn A. Williams; Michael W. Meyer; Anton M. Scheuhammer; Nina Schoch; Andrew T. Gilbert; Lori Siegel; Robert J. Taylor; Robert Poppenga; Christopher R. Perkins (Ecotoxicology, 2011)

Do partially buried dune plants grow in optimal trajectories? - M. E. Gilbert; N. W. Pammenter; B. S. Ripley (Plant Ecology, 2011)

In vitro hepatoprotective and antioxidant activities of crude extract and isolated compounds from Ficus gnaphalocarpa - Donfack J. Hubert; Amadou Dawe; Ngueguim T. Florence; Kapche D. W. F. Gilbert; Tchana N. Angele; D. Buonocore; P. Vita Finzi; G. Vidari; Ngadjui T. Bonaventure; Fulvio Marzatico; Moundipa F. Paul (Inflammopharmacology, 2011)

Spatial distribution of soil phosphorus and herbage mass in beef cattle pastures: effects of slope aspect and slope position - Gilbert C. Sigua; Samuel W. Coleman; Joseph Albano; Mimi Williams (Nutrient Cycling in Agroecosystems, 2011)

Factors Influencing Safety Among a Group of Commercial Fishermen Along the Texas Gulf Coast - Jeffrey L. Levin; Karen Gilmore; Sara Shepherd; Amanda Wickman; Ann Carruth; J. Torey Nalbone; Gilbert Gallardo; Matthew W. Nonnenmann (Journal of Agromedicine, 2010)

The byssus of the zebra mussel ( Dreissena polymorpha ): spatial variations in protein composition - Trevor W. Gilbert; Eli D. Sone (Biofouling, 2010)

Nitrogen in soils, plants, surface water and shallow groundwater in a bahiagrass pasture of Southern Florida, USA - Gilbert C. Sigua; Robert K. Hubbard; Samuel W. Coleman; Mimi Williams (Nutrient Cycling in Agroecosystems, 2010)

Spatial distribution of soil carbon in pastures with cow-calf operation: effects of slope aspect and slope position - Gilbert C. Sigua; Samuel W. Coleman (Journal of Soils and Sediments, 2010)

Quantifying phosphorus levels in soils, plants, surface water, and shallow groundwater associated with bahiagrass-based pastures - Gilbert C. Sigua; Robert K. Hubbard; Samuel W. Coleman (Environmental Science and Pollution Research, 2010)

Mechanical damage to pollen aids nutrient acquisition in Heliconius butterflies (Nymphalidae) - Harald W. Krenn; Monika J. B. Eberhard; Stefan H. Eberhard; Anna-Laetitia Hikl; Werner Huber; Lawrence E. Gilbert (Arthropod-Plant Interactions, 2009)

Quantifying soil organic carbon in forage-based cow–calf congregation-grazing zone interface - Gilbert C. Sigua; Samuel W. Coleman; Joseph P. Albano (Nutrient Cycling in Agroecosystems, 2009)

Palaeoenvironment reconstruction, volcanic evolution and geochronology of the Cerro Blanco subcomplex, Nevados de Chillán volcanic complex, central Chile - Katy Mee; Jennie S. Gilbert; David W. McGarvie; José A. Naranjo; Malcolm S. Pringle (Bulletin of Volcanology, 2009)

Can Campylobacter coli induce Guillain-Barré syndrome? - A. van Belkum; B. Jacobs; E. van Beek; R. Louwen; W. van Rijs; L. Debruyne; M. Gilbert; J. Li; A. Jansz; F. Mégraud; H. Endtz (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

The Fallout from Fireworks: Perchlorate in Total Deposition - Jennie Munster; Gilbert N. Hanson; W. Andrew Jackson; Srinath Rajagopalan (Water, Air, & Soil Pollution, 2009)

Potential for phosphonoacetate utilization by marine bacteria in temperate coastal waters - Jack A. Gilbert; Simon Thomas; Natalie A. Cooley; Anna Kulakova; Dawn Field; Tim Booth; John W. McGrath; John P. Quinn; Ian Joint (Environmental Microbiology, 2009)
Summary Phosphonates are organic compounds that contain a C–P bond and are a poorly characterized component of the marine phosphorus cycle. They may represent a potential source of bioavailable phosphorus, particularly in oligotrophic conditions. This study has investigated the distribution of the phnA gene which encodes phosphonoacetate hydrolase, the enzyme that mineralizes phosphonoacetate. Using newly designed degenerate primers targeting the phnA gene we analysed the potential for phosphonoacetate utilization in DNA and cDNA libraries constructed from a phytoplankton bloom in the Western English Channel during July 2006. Total RNA was isolated and reverse transcribed and phosphonoacetate hydrolase ( phnA ) transcripts were PCR amplified from the cDNA with the degenerate primers, cloned and sequenced. Phylogenetic analysis demonstrated considerable diversity with 14 sequence types yielding five unique phnA protein groups. We also identified 28 phnA homologues in a 454‐pyrosequencing metagenomic and metatranscriptomic study from a coastal marine mesocosm, indicating that > 3% of marine bacteria in this study contained phnA . phnA homologues were also present in a metagenomic fosmid library from this experiment. Finally, cultures of four isolates of potential coral pathogens belonging to the Vibrionaceae contained the phnA gene. In the laboratory, these isolates were able to grow with phosphonoacetate as sole P and C source. The fact that the capacity to utilize phosphonoacetate was evident in each of the three coastal environments suggests the potential for widespread utilization of this bioavailable P source.

Effect of rotation on colonization of field stubble by Fusarium species - Saber Golkari; Jeannie Gilbert; Kirsten Slusarenko; W. Fernando; Anita Brûlé-Babel (Cereal Research Communications, 2008)

Large rivers do not always act as species barriers for Lepilemur sp. - Mathias Craul; Ute Radespiel; David W. Rasolofoson; Gilbert Rakotondratsimba; Odon Rakotonirainy; Solofonirina Rasoloharijaona; Blanchard Randrianambinina; Jonah Ratsimbazafy; Felix Ratelolahy; Tahirihasina Randrianamboavaonjy; Lucien Rakotozafy (Primates, 2008)

An explosive–intrusive subglacial rhyolite eruption at Dalakvísl, Torfajökull, Iceland - H. Tuffen; D. W. McGarvie; H. Pinkerton; J. S. Gilbert; R. A. Brooker (Bulletin of Volcanology, 2008)

Promiscuous, non-catalytic, tandem carbohydrate-binding modules modulate the cell-wall structure and development of transgenic tobacco (Nicotiana tabacum) plants - Olawole O. Obembe; Evert Jacobsen; Jaap Timmers; Harry Gilbert; Anthony W. Blake; J. Paul Knox; Richard G. F. Visser; Jean-Paul Vincken (Journal of Plant Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Identification of host range mutants of myxoma virus with altered oncolytic potential in human glioma cells - John W Barrett; Lindsay R Alston; Fuan Wang; Marianne M Stanford; Philippe-Alexandre Gilbert; Xiujuan Gao; June Jimenez; Danielle Villeneuve; Peter Forsyth; Grant McFadden (Journal of NeuroVirology, 2007)

Biotic interactions and plant invasions - Charles E. Mitchell; Anurag A. Agrawal; James D. Bever; Gregory S. Gilbert; Ruth A. Hufbauer; John N. Klironomos; John L. Maron; William F. Morris; Ingrid M. Parker; Alison G. Power; Eric W. Seabloom; Mark E. Torchin; et al. (Ecology Letters, 2006)
Introduced plant populations lose interactions with enemies, mutualists and competitors from their native ranges, and gain interactions with new species, under new abiotic conditions. From a biogeographical perspective, differences in the assemblage of interacting species, as well as in abiotic conditions, may explain the demographic success of the introduced plant populations relative to conspecifics in their native range. Within invaded communities, the new interactions and conditions experienced by the invader may influence both its demographic success and its effects on native biodiversity. Here, we examine indirect effects involving enemies, mutualists and competitors of introduced plants, and effects of abiotic conditions on biotic interactions. We then synthesize ideas building on Darwin's idea that the kinds of new interactions gained by an introduced population will depend on its relatedness to native populations. This yields a heuristic framework to explain how biotic interactions and abiotic conditions influence invader success. We conclude that species introductions generally alter plants’ interactions with enemies, mutualists and competitors, and that there is increasing evidence that these altered interactions jointly influence the success of introduced populations.

Subglacial and ice-contact volcanism at the Öræfajökull stratovolcano, Iceland - John A. Stevenson; David W. McGarvie; John L. Smellie; Jennie S. Gilbert (Bulletin of Volcanology, 2006)

Differentially expressed genes associated with dormancy or germination of Arabidopsis thaliana seeds - Peter E. Toorop; Rosa Maria Barroco; Gilbert Engler; Steven P. C. Groot; Henk W. M. Hilhorst (Planta, 2005)

Catchment–coastal zone interaction based upon scenario and model analysis: Elbe and the German Bight case study - J. Hofmann; H. Behrendt; A. Gilbert; R. Janssen; A. Kannen; J. Kappenberg; H. Lenhart; W. Lise; C. Nunneri; W. Windhorst (Regional Environmental Change, 2005)

Assessing the efficacy of dredged materials from lake panasoffkee, Florida: Implication to environment and agriculture - Gilbert C. Sigua; Mike L. Holtkamp; Samuel W. Coleman (Environmental Science and Pollution Research, 2004)

Assessing the efficacy of dredged materials from lake panasoffkee, florida: Implication to environment and agriculture part 1: Soil and environmental quality aspect - Gilbert C. Sigua; Mike L. Holtkamp; Samuel W. Coleman (Environmental Science and Pollution Research, 2004)

Wetland conversion to beef cattle pasture changes in soil properties - Gilbert C. Sigua; Jim Griffin; Woo-jun Kang; Samuel W. Coleman (Journal of Soils and Sediments, 2004)

Chemical Contaminants and their Effects in Fish and Wildlife from the Industrial Zone of Sumgayit, Republic of Azerbaijan - Carol D. Swartz; K.C. Donnelly; Arif Islamzadeh; Gilbert T. Rowe; William J. Rogers; Grigoriy M. Palatnikov; Arif A. Mekhtiev; Rafik Kasimov; Thomas J. McDonald; Jeffery K. Wickliffe; Bobby J. Presley; John W. Bickham (Ecotoxicology, 2003)

Editorial: The Unknown Environmental Tragedy in Sumgayit, Azerbaijan - John W. Bickham; Cole W. Matson; Arif Islamzadeh; Gilbert T. Rowe; K.C. Donnelly; Carol D. Swartz; William J. Rogers; Jeffrey K. Wickliffe; Robin L. Autenrieth; Thomas J. McDonald; Dmitri Politov; Grigoriy Palatnikov; et al. (Ecotoxicology, 2003)

Knowledge Recovery for Continental-Scale Mineral Exploration by Neural Networks - Laurent Bougrain; Maria Gonzalez; Vincent Bouchot; Daniel Cassard; Andor L. W. Lips; Frédéric Alexandre; Gilbert Stein (Natural Resources Research, 2003)

Land Application of Lake-Dredged Materials for Bahiagrass Establishment in the Subtropical Beef Pasture - Gilbert C. Sigua; Mike L. Holtkamp; John M. Linton; Samuel W. Coleman (Journal of Soils and Sediments, 2003)

Direct and indirect effects of juvenile Buenoa macrotibialis (Hemiptera: Notonectidae) on the zooplankton of a shallow pond - Stephanie E. Hampton; John J. Gilbert; Carolyn W. Burns (Limnology and Oceanography, 2000)
We investigated the effects of juvenile Buenoa macrotibialis on the small bodied ( Buenoa over 9–12 d, we found that second and fourth instar Buenoa caused large declines in the copepod Tropocyclops extensus and the rotifer Hexarthra mira . Additionally, populations of several small rotifers increased in the presence of fourth instar Buenoa , probably because of release from Tropocyclops predation, competition, or both.

Deconvolution with wavelets and vaguelettes - A. Gilbert; W. Keller (Journal of Geodesy, 2000)

The Use of Atmospheric Dispersion Models in Risk Assessment Decision Support Systems for Pesticides - Frank A. A. M. de Leeuw; W. Addo J. van Pul; Frederik van den Berg; Andrew J. Gilbert (Environmental Monitoring and Assessment, 2000)

Summer distribution patterns of the backswimmer, Anisops wakefieldi (Hemiptera: Notonectidae), in a New Zealand pond - John J. Gilbert; Carolyn W. Burns; Caroline C. Gilbert (New Zealand Journal of Marine and Freshwater Research, 1999)
The relative abundance of different‐sized Anisops wakefieldi in a small, fishless pond was determined from sweep‐net samples taken along one open‐water and two shoreline transects at noon on two dates, and at noon and midnight on a third date. During the day, large individuals occurred only along the shore, whereas smaller ones occurred both along the shore and in open water. At night, large individuals also occurred in the open water. The diurnal size‐class segregation suggests that young individuals migrate into less preferred, open water to avoid interference and cannibalism from larger individuals. The shoreline may be preferred during the day because it provides greater food resources or a refuge from visually feeding avian predators. Laboratory experiments in containers with floating aquatic plants at one end complemented the field data. When alone, both small and large A. wakefieldi sought cover during the day and moved into open water at night. During the day, the presence of large individuals induced small ones to move into open water. The results of this study on a notonectid population are consistent with some earlier ones in demonstrating that interactions between large and small size classes may lead to pronounced spatial segregation of size classes, and show for the first time that spatial distributional patterns during the day and night may be very different.

The neurobeachin gene ( Nbea ) identifies a new region of homology between mouse central Chromosome 3 and human Chromosome 13q13 - Debra J. Gilbert; Hartmut Engel; Xiaolu Wang; Karl-Heinz Grzeschik; Neal G. Copeland; Nancy A. Jenkins; Manfred W. Kilimann (Mammalian Genome, 1999)

Some observations on the diet of the backswimmer, Anisops wakefieldi (Hemiptera: Notonectidae) - John J. Gilbert; Carolyn W. Burns (Hydrobiologia, 1999)

Allylmalonamide as a bivalent linker: Synthesis of biantennary GM3-saccharide—Keyhole limpet hemocyanin glycoconjugate and the immune response in mice - Wei Zou; Mary Abraham; Michel Gilbert; Warren W. Wakarchuk; Harold J. Jennings (Glycoconjugate Journal, 1999)

Chromosomal location and tissue expression of the gene encoding the adenovirus E1A-regulated transcription factor E4F in humans and mice - Robert J. Rooney; Rachael R. Daniels; Nancy A. Jenkins; Debra J. Gilbert; Kristen Rothammer; Stephan W. Morris; Douglas R. Higgs; Neal G. Copeland (Mammalian Genome, 1998)

Purification and characterization of the recombinant CMP-sialic acid synthetase from Neisseria meningitidis - Michel Gilbert; David C. Watson; Warren W. Wakarchuk (Biotechnology Letters, 1997)

Summary of Discussions at a Conference on Rhizoctonia Held at Twin Falls, Idaho, Feb. 24, 1977 - W. J. Hooker; Gilbert J. Banville; A. R. Weinhold; Tully Bowman; D. H. Hall; Gene D. Easton; J. R. Davis; James A. Frank (American Journal of Potato Research, 1978)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

Lactate dehydrogenase in one-cell rabbit embryos extracted with triton X-100 - Timothy A. R. Peacock; Gilbert A. Schultz; Leon W. Browder (Biochemical Genetics, 1976)

Lactate dehydrogenase in preimplantation rabbit embryos - Gilbert A. Schultz; Leon W. Browder (Biochemical Genetics, 1975)

RNA virus-like particles in the chytridiomycete Allomyces arbuscula - Edward W. Khandjian; Urs-Peter Roos; William E. Timberlake; Lorenza Eder; Gilbert Turian (Archives of Microbiology, 1974)

Potato notes - C. Tice; H. G. Zuckerman; W. C. Edmundson; W. L. Floyd; G. W. Waller; A. J. Johnston; E. P. Miller; E. A. Stokdyk; G. L. Tiebout; H. C. Moore; Walter M. Peacock; Andrew Schnetzler; et al. (American Journal of Potato Research, 1925)

Potato notes - C. Tice; A. J. Johnston; E. P. Miller; E. A. Stokdyk; J. W. Weston; A. G. Tolass; J. Norton Woodruff; Ellwood Douglass; Wm. H. Martin; W. S. Blair; N. W. Glines; J. Tucker; et al. (American Journal of Potato Research, 1924)

Potato notes - C. W. Tice; J. T. Rosa; A. E. Wilkinson; E. A. Stokdyk; E. L. Newdick; Verdal T. Maxwell; C. F. Clark; W. Stuart; Charles A. Thompson; J. Gilbert Borton; Ellwood Douglass; Orley G. Bowen; et al. (American Journal of Potato Research, 1924)

Potato notes - J. T. Rosa; E. A. Stokdyk; H. J. Wheeler; J. F. Hockey; H. O. Werner; W. H. Martin; O. G. Bowen; J. Gilbert Barton; Wm. B. Duryee; J. C. Crissey; A. H. C. Odell; C. R. Inglee; et al. (American Journal of Potato Research, 1924)

Seed certification notes - M. F. Barrus; W. Stuart; A. W. Tompkins; A. H. Gilbert; J. G. Milward (American Journal of Potato Research, 1924)